Multipotent stem cells from umbilical cord: Cord is richer than blood! - Secco, Mariane (2008)
The identification of mesenchymal stem cell ( MSC) sources that are easily obtainable is of utmost importance. Several studies have shown that MSCs could be isolated from umbilical cord (UC) units. However, the presence of MSCs in umbilical cord blood (UCB) is controversial. A possible explanation for the low efficiency of MSCs from UCB is the use of different culture conditions by independent studies. Here, we compared the efficiency in obtaining MSCs from unrelated paired UCB and UC samples harvested from the same donors. Samples were processed simultaneously, under the same culture conditions. Although MSCs from blood were obtained from only 1 of the 10 samples, we were able to isolate large amounts of multi-potent MSCs from all UC samples, which were able to originate different cell lineages. Since the routine procedure in UC banks has been to store the blood and discard other tissues, such as the cord and/or placenta, we believe our results are of immediate clinical value. Furthermore, the possibility of originating different cell lines from the UC of neonates born with genetic defects may provide new cellular research models for understanding human malformations and genetic disorders, as well as the possibility of testing the effects of different therapeutic drugs.